VIVÊNCIAS DE MÃES DE CRIANÇAS SUBMETIDAS À CIRURGIA CARDÍACA NA UNIDADE DE TERAPIA INTENSIVA CARDIOLÓGICA DO HOSPITAL UNIVERSITÁRIO - Salgado, Christiana Leal (2010)
This paper aims to analyze the experience of young children s families in the face of an intensive Care Unit of Cardiology s internment. The presence of parents in the hospital environment contributes to minimize the suffering caused by the child's hospitalization. Understanding the factors that help parents when facing the context of disease treatment and hospitalization of a child can help them to understand the dynamic factors related to hospital, helping them to better cope with the situation of illness, treatment and hospitalization. Qualitative approach was the methodological option, considering the nature of study s subject. Were accomplished six semistructured interviews with mothers and a father besides 100 hours of participant observation during the study, 20 hours of it dedicated to formal observation. We used the thematic analysis, a method of content analysis to understand the data. The results were classified into four units of meaning: feelings and emotions against the child's illness; heart disease under the maternal staring; the mother and child in the dynamics of the Intensive Care Unit; resources to face the situation; It follows that the heart s symbolism enhances the mothers emotional fragility regarding their children's illness; religiosity; spirituality and a consistent social support network were contributing factors for demonstration and maintenance of adaptive behavior. The presence of the mother and her stay in all stages of children s treatment in the studied Unit does not always happen.